STUDI EKPLORASI PADA DESA WISATA PENGLIPURAN KABUPATEN BANGLI - Ida Bagus Naba; Ida Bagus Gede Paramita (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
An exploratory study in the Penglipuran tourist village, Bangli Regency, uses an ethnographic approach, which is an empirical approach to the society and culture of the people in the Penglipuran tourism village. This research is a qualitative research. Collecting data using interview methods, documentation observation and literature study. The method of analysis, carried out in a descriptive-qualitative way by using the working stages of the sociology of tourism theory, namely by examining the characteristics, motivations and typology of tourists who make tourist visits to Penglipuran village. The results of the analysis are presented in a systematic and structured manner. The results of this study provide an answer that the arrival of tourists to the tourist village of Penglipuran is because they are interested in the existing traditional architecture, including cultural survival of traditional houses, clean villages and provide a sense of comfort to tourists.Keywords: Exploration, Penglipuran, Characteristics, Motivation, Typology